2018
DOI: 10.1136/gutjnl-2018-316678
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic circulating markers of inflammation and risk of oesophageal adenocarcinoma: a study within the National Cancer Institute Cohort Consortium

Abstract: This prospective study provides evidence of a link between systemic inflammation and oesophageal adenocarcinoma risk. In addition, this study provides the first evidence that indirect effects of excess adiposity and cigarette smoking, via systemic inflammation, increase the risk of oesophageal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…The multicohort study by Cook et al . using the above mentioned Luminex bead‐based assay (with 31 overlapping biomarkers) shared no significant associations with our study . These results further support the major etiologic differences between the two histologic subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The multicohort study by Cook et al . using the above mentioned Luminex bead‐based assay (with 31 overlapping biomarkers) shared no significant associations with our study . These results further support the major etiologic differences between the two histologic subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, other studies revealed that IL-17A can enhance the tumor killing capability via humoral cell-mediated induction of immunogenic antibody and cytolytic molecules in ESCC [52]. Though, the role of circulating IL-17 or IL-22 in esophageal cancers is not yet defined [36] and further studies are needed to clarify the role of IL-17A and IL-22 in EACs.…”
Section: Plos Onementioning
confidence: 94%
“…A general limitation in analyzing systemic interleukins lies in the high number of confounding factors potentially influencing systemic interleukin levels. For example, Cook et al recently described a potential link between excessive obesity and cigarette smoking with systemic inflammation [36]. Also, other environmental factors like alcohol or the composition of the microbiota might alter systemic inflammation.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in our recent study of 2 US cohort studies, we reported that overweight in early adulthood and weight gain in later life were associated with increased EA and GCA risk . Although the underlying mechanisms of the BMI‐EA/GCA association are unclear, leading hypotheses include mediation by gastroesophageal reflux or metabolic dysfunction .…”
Section: Introductionmentioning
confidence: 98%